2014
DOI: 10.1016/b978-0-12-416022-4.00004-4
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Stem Cells in Adult Skin

Abstract: The skin is the first line of defense against dehydration and external environmental aggressions. It constantly renews itself throughout adult life mainly due to the activity of tissue-specific stem cells. In this review, we discuss fundamental characteristics of different stem cell populations within the skin and how they are able to contribute to normal skin homeostasis. We also examine the most recent results regarding the cell-intrinsic and -extrinsic components of the stem cell niche within the adult skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 132 publications
0
36
0
Order By: Relevance
“…In addition, expression of the Wnt ligand, Wnt 7b, and the downstream Wnt effector/target gene, LEF1, were up-regulated following poly (I:C) treatment of keratinocytes (Fig. 5C–E) (Barker and Clevers, 2010; Tadeu and Horsley, 2014). Similarly, expression of Shh pathway components SHH and GLI1 was increased following poly (I:C) addition, as was the expression of EDAR, another gene active in skin appendage formation (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, expression of the Wnt ligand, Wnt 7b, and the downstream Wnt effector/target gene, LEF1, were up-regulated following poly (I:C) treatment of keratinocytes (Fig. 5C–E) (Barker and Clevers, 2010; Tadeu and Horsley, 2014). Similarly, expression of Shh pathway components SHH and GLI1 was increased following poly (I:C) addition, as was the expression of EDAR, another gene active in skin appendage formation (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Following treatment with poly (I:C), keratinocytes expressed markers associated with hair progenitors including leucine-rich-repeat containing G proteins (LGR) 5 and 6 (Fig 4F) (Tadeu and Horsley, 2014). Induction of LGR6 is particularly notable, as previous lineage tracing experiments demonstrated that LGR6 expressing cells contribute to regenerating hair follicles during WIHN (Snippert et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the IFE, these long-lived ESC give rise to progenitors with increased proliferative capacities that differentiate into keratinocytes as they migrate upward into suprabasal layers. Numerous studies have addressed the role of several key signaling pathways, such as those implicating bone morphogenetic proteins, TGF-β, Notch, Sonic Hedgehog, or Wnt in skin homeostasis, and how they control ESC maintenance (1)(2)(3). The role of these pathways in regulating stemness has been attributed to the regulation of cell proliferation, cell death, cellular senescence, cell adhesion, or differentiation.…”
mentioning
confidence: 99%
“…The outer epithelial layer of human skin is continuously developed and renewed by differentiating basal layer stem cells (Tadeu and Horsley, 2014). Accordingly, every day humans shed significant numbers of cells that contain DNA, epidermal proteins and mRNA.…”
Section: Introductionmentioning
confidence: 99%